Integration of Character Values in Physical Education Learning: An Analysis Databased on GARUDA (Gerba Rujukan Digital) - Yusuf, Fahri; Azhariat, Citra; Bhakti, Yopi Hutomo; Yulisatria, Guntur; Suhariyanti, Mela; Anwar, Khamdan (STKIP Pasundan, 2025)
This study examines scientific evidence on the integration of character values in Physical Education, Sports, and Health (PJOK) learning in Indonesia. Using a Systematic Literature Review approach guided by PRISMA, data were collected from the Garba Rujukan Digital (Garuda) database covering publications from 2010 to 2025. Inclusion criteria focused on Indonesian-language journal articles that explicitly discussed character value integration in PJOK at various educational levels. Fifteen eligible articles were analyzed. Findings show a notable rise in publications between 2021 and 2025, indicating increasing academic attention to character education through PJOK. Dominant values integrated include discipline, responsibility, cooperation, honesty, and sportsmanship, while social care, peaceful attitudes, and religiosity are less represented. Successful implementation is influenced by teacher role modeling, consistent positive habits, and reflective learning strategies. Overall, PJOK functions as a strategic medium for holistic character development that combines physical, social, emotional, and moral dimensions to cultivate healthy and resilient students.